The Types, Regional Distribution, and Consumption Trend of Chinese Traditional Wheat-Based Foods - Yu Gao; Xiulin Wang; Yan Shi (Journal of Food Quality)
Chinese wheat-based foods have a long history and a wide range of varieties, which is representative of Chinese food culture. Pasta and bread are made of wheat flour, and the characteristics of pasta and bread are closely related to the quality of wheat flour. The quality of wheat is mainly affected by environmental conditions, and different varieties of wheat are suitable for planting in different regions, so the regionalization of wheat is formed. Due to the different quality of wheat and eating habits in different regions of China, the same kind of wheat-based foods has different flavors in different regions, such as steamed bread, noodles, and stuffed buns. The regional characteristics of food are also formed between different regions. For example, Naan. With the changes in Chinese people’s eating habits and consumption level, there are more and more types of wheat-based foods, which are developing in the direction of industrialization. This review clarifies the wheat planting regionalization in China, giving an insight into the relationship between different wheat quality and the variety of traditional wheat-based foods, describing the types and regional distribution of traditional wheat-based food products in China. Moreover, the types of wheat-based foods are classified and whose characteristics are introduced, and the consumption trend of wheat-based foods in China is elaborated.